PSYCHOLOGICAL ANALYSIS OF PROFESSIONAL QUALITIES OF TEACHERS - Kaminska, Olga (PSYCHOLOGICAL JOURNAL, 2016)
The analysis of psychological characteristics that improve increase of a teacher’s efficiency and optimize the process of its professional functions realization is carried out in the article. The totality of professional important qualities that promote to the personality’s successful self-realisation identity in the field of pedagogics is determined. The role of such characteristics as tolerance, low conflict, confidence, sociability, empathy, reflexivity, emotional stability is made clear in the process of the teacher’s professional self-realisation. The necessity of these characteristics development in the context of realisation of the personal-oriented approach which allows to establish and to maintain harmonious mutual relation with the subjects of the pedagogical process, to expose a student’s potential, to direct it to development and improvement of its skills. It was determined that humanization of education, which is manifested actively in recent years, requires reconstruction by the teachers of various aspects of their activities. First of all, consciousness of own important professional qualities based on reflection should be in the centre of this reconstruction. The teacher’s professiograms, proposed by different authors are analyzed. The place in the system of the self-realised tendencies of a teacher, qualities of social and professional pedagogical orientation, appropriate skills and abilities (structural, organizational, communication, research, applied). The impact on the process of effective activity of a teacher of psychological, social, physical, scientific, theoretical and practical readiness is determined. The attention to the personal qualities of a teacher that improve efficiency of his professional activity is focused. The author of the article emphasized that the basis of pedagogical competence of teacher is combination of personal features and characteristics that ensure efficient performance of professional functions, create preconditions for personal growth, establish constructive contacts with the subjects of pedagogical interaction.